Predation on mangrove propagule under four light intensity habitats in Kabili-Sepilok and Elopura Forest Reserves, Sabah - Chong, Fung Yun; Kueh, Roland Jui Heng; Mojiol, Russel @ Andy Immit (Sabah Forestry Department, 2014)
Mangroves generally occupy a narrow niche between the marine and terrestrial environment. In this environment, seed predation is more important than microsite competition because it determines the plant population. A study on propagule predation, especially to look into the mortality percentages of mangrove tree species is important in order to find out the factors that affect the establishment of mangrove seedlings. Four study sites were established at the Kabili-Sepilok & Elopura riverbanks. Six species, namely Bruguiera sexangula, B. parvifolia, B. gymnorrhiza, Ceriops tagal, Rhizophora apiculata and R. mucronata were investigated. Within each site, four replicates of 5 x 5 m plots were established with 6 individual propagules randomly selected from each species and planted vertically. The survival status of propagules, namely eaten, washed away and no changes were observed and recorded in a period of 45 days. The study sites selected were naturally found to have small gap 7 × 7m, big gap 15 × 15m, closed canopy 50% and shaded canopy 80%. Our findings showed mortality percentages of propagules caused by predators have the least in small gap 7 × 7m < big gap 15 × 15m < closed canopy 80% <shaded canopy 50%. Propagules of Bruguiera sexangula and B. parvifolia were the most consumed. In conclusion, propagule predators, mainly crabs were the major cause of mortality and this predation is less serious in smaller gaps.